Kafalah Penanggungan pada Konsep Fikih dan Aplikasinya dalam Ekonomi Syariah - Endang Zakaria; Hikmah Dwi Astuti (Jurnal At Taajir, 2022)
In general, kafalah is a gurantee from a guarantor (a third party), both in the form of personal and property guarantees to a second party in connection with the rights and obligation of the second party to another party (the first party). Kafalah is carried out with the insurer, the main guarantor, the party whose rights are borne, and the dependents. The primary source of this research is literature, using a descriptive qualitative approach. The scholars of madhhab allow this kafalah contract. The Muslims of Nubuwwah’s time practiced this, even today, without any objection from a scholar. The permissibility of the kafalah contract in Islam is also based on human needs and at the same time negates the existence of harm to people in need. Kafalah is also included in one of the form os self-guarantee of the Islamic banking facitilies, which is a guarantee from the guarantor in the form of self-guarantee or goods for obligations borne by other parties. The permissibility of kafalah as one of the Islamic banking products is also based on the texts of the Qur’an al Karim, the hadiths of the Prophet Muhammad and several opinions of jumhur fuqaha’.